COMPARATIVE EFFECTIVENESS OF NEURAXIAL ANESTHESIA TECHNIQUES IN OBESE PARTURIENT WOMEN WITH PREGNANCY-INDUCED HYPERTENSION UNDERGOING CESAREAN SECTION - Nematulloev Tukhtasin Komiljonovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: To evaluate the efficacy of various neuraxial anesthesia techniques in parturient women with obesity and pregnancy-induced hypertension (PIH) undergoing cesarean section (CS). A retrospective analysis was conducted on data from 110 parturient women with obesity and PIH who had CS. The participants were categorized into three groups based on the type of neuraxial anesthesia used: spinal anesthesia (SA), epidural anesthesia (EA), and combined spinal-epidural anesthesia (CSE). Clinical variables were assessed and compared across these groups. The average age of the patients was 30 years. Women in the CSE group experienced a longer time from puncture to surgery, smaller intraoperative fluctuations in mean arterial pressure, higher Apgar scores at both 1 and 5 minutes, shorter surgery durations, and lower incidences of nausea, vomiting, and intraoperative hypotension compared to those in the SA and EA groups. Although CSE takes more time to administer in parturient women with obesity and PIH undergoing CS compared to SA or EA, it offers several significant advantages. These include a reduction in surgery time, more stable intraoperative mean arterial pressure, decreased rates of nausea, vomiting, and intraoperative hypotension, and improved Apgar scores at 1 and 5 minutes.